Кримінально-правові питання приведення вироку суду іноземної держави у відповідність із законодавством України (визначення статей КК України) - Лащук, Н; Lashchuk, N (СНУ ім.Лесі Українки, 2019)
У статті досліджено особливості виконання вироків судів іноземних держав, а саме приведення вироку суду іноземної держави у відповідність із законодавством України. Запропоновано критерії встановлення відповідності суспільно-небезпечних діянь, вказаних у вироках судів іноземних держав, із КК України. При визначенні статті (частини статті) закону України про кримінальну відповідальність, якими передбачена відповідальність за злочин, вчинений громадянином України, засудженим судом іноземної держави, слід виділити встановлені фактичні обставини справи. Після чого потрібно вивести формулу кваліфікації відповідно до КК України, на підставі того, що в літературі іноді називають «фактичним складом злочину», з врахуванням впливу інститутів Загальної частини КК. The procedure for the transfer of the Ukrainian citizens sentenced by foreign courts for committing crimes is regulated by multilateral international treaties and bilateral agreements between Ukraine and other states, the Criminal Procedure Code of Ukraine, the Criminal Code of Ukraine and other normative-legal acts. First of all, among the existing international legal acts the multilateral agreements the European Convention on the Transfer of Sentenced Persons 1983 (in force in Ukraine since January 1, 1996) and the European Convention on the International Validity of Criminal Sentences, 1970 (valid in Ukraine since 12 June 2003) are particularly important for this study. Such a procedure involves bringing the sentence of the foreign state court into conformity with the legislation of Ukraine (determination of the norms of the Criminal Code of Ukraine provides for an act described in the verdict of a court of a foreign state). It is necessary to take into account the facts of the case provided by the court of a foreign state in determining the article (paragraph of the article) of the Ukrainian law on criminal liability, which envisages penalties for a criminal offense committed by a convicted citizen of Ukraine. Then we need to derive a crime qualification formula in accordance with the Criminal Code of Ukraine, on the grounds of what is sometimes referred to as «actual crime» in the literature. In this case, it is necessary to take into account: 1) the dissemination of the international treaties provisions regulating the issues of crime committed before entry into force of the contractual obligations of the states; 2) the validity of the Criminal Code of Ukraine in time regarding the acts specified in the verdict of the court of a foreign state; 3) the characteristics of the perpetrator, including the age, with criminal responsibility in Ukraine; 4) provisions relating to the stages of the commission of a crime, the institution of plurality, complicity.
Procedure of Bringing the Verdict of a Foreign State in Conformance with the Laws of Ukraine: Criminal Legal Issues (the Definition of Articles in the Criminal Code of Ukraine)
Keywords: міжнародна співпраця; вирок суду іноземної держави; законодавство іноземної держави; Кримінальний кодекс України; приведення у відповідність із законодавством України; international cooperation; the verdict of a foreign state court; the legislation of a foreign state; the Criminal Code of Ukraine; bringing the verdict in conformance with the legislation of Ukraine